2022
DOI: 10.3390/vaccines10030385
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response of SARS-CoV-2 Infection and Anti-SARS-CoV-2 Vaccination in Renal Transplant Recipients

Abstract: Vaccination-induced SARS-CoV-2 neutralizing antibodies are required for herd immunity. Vaccine availability and poor vaccine response in renal transplant recipients (RTRs) remain a concern. There is no report on the efficacy of Covaxin and Covishield vaccines in RTRs. We recruited 222 live donors RTRs and analyzed the serum titer of anti-SARS-CoV-2 spike protein antibody by chemiluminescent magnetic microparticle immunoassay. Patients were categorized into three groups: group1 with SARS-CoV-2 infection and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Alternatively, using more antigenic material in vaccine preparation may improve the vaccine efficacy for these patients. The present two-center study confirms the finding of our single-center study of higher seroconversion rate with COVISHIELD™ and COVAXIN™ in living donor renal transplant patients in India ( 10 ). The side-effects profile suggests the safety of these vaccines in RTRs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alternatively, using more antigenic material in vaccine preparation may improve the vaccine efficacy for these patients. The present two-center study confirms the finding of our single-center study of higher seroconversion rate with COVISHIELD™ and COVAXIN™ in living donor renal transplant patients in India ( 10 ). The side-effects profile suggests the safety of these vaccines in RTRs.…”
Section: Discussionsupporting
confidence: 91%
“…The lower antibody titer may be due to the waning of the antibody over time ( 3 , 37 ). It is speculated that whole virus-based vaccines may induce the robust seroconversion and elicitation of antibody titer as reflected in our finding ( Table 2 ) ( 10 ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our study has shown that a large proportion of KTRs had an asymptomatic infection before vaccination. The balance of participants with asymptomatic infection was 78% in our study, which is comparable to 90% found by Prasad et al in another Indian study [ 12 ]. A large study has shown that 90% of infections in India are asymptomatic [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Vaccine response to mRNA vaccines is poor in organ transplant recipients. [ 54 ] However, one published[ 55 ] and our unpublished data from India have shown excellent seroconversion rates (>80%) even with single dose of Oxford-Astra Zeneca vaccine. This may be related to the younger age, lower comorbidity burden, and possibly high rates of symptomatic and subclinical infection.…”
Section: Vaccinationmentioning
confidence: 98%